Aprimoramento da eficiência de um sistema de geração de energia elétrica por grupo gerador alimentado com gás pobre - Bezerra, Alexandre Freire (2016)
certainly, not all people on our planet have access to electricity, especially those located in remote communities of large cities. The solution to this issue, usually meets economic difficulties, due to the frequent increase in the prices of traditional fuels, or long droughts in countries where the main source is the hydroelectric. In such cases, the usually idea to overcome the problem has in the alternative energy the easiest and the cheapest solution. So in a country like ours, where biomass has made possible the generation of industrial energy, either through sugarcane bagasse, coconut shells, eucalyptus, etc., we see the possibility of expand this potential through the use of the biomass gasification technology. RUMÃO 2013, fueling a converted diesel engine MWM D229-4, not only expanded the limit of electricity generation established by the Indian gasifier builders, but improved the performance of the gasifier system/engine/generator. The purpose of the present study was to promote advances in the parameter values obtained by RUMÃO 2013 creating a map based on the engine power and on the admission angle, to guarantee fuel consumption reduction. For this purpose, it was used the commercial FT 400 ignition controller. Moreover, we took care of the thermal insulation of the pipe that leads the poor gas to the engine, and incorporated into the gasifier before the cloth filter system, a gas reservoir with two purposes: to prevent the fabric of the filter to be water clogged, and to create a gas storage for the engine higher demands. After the introduction of these innovation tests were conducted and all results were compared with those of Rumão 2013: consumption was reduced by 0,512 kg/kW.h at an angle of 9° and power of 13 kWe; regarding the thermal efficiency just of the gasifier Rumão presented better results, but when it came to the system formed by the gasifier system and generator, which really counts, our results overpassed those of Rumão 2013 in 7%, reaching 27%; for all advance angles chosen gave electric power higher than that of Rumão 2013; the best result happened at the ignition angle or 7° resulting in 29 kWe. This map was constructed from the ignition angles which provided lower consumption in biomass power ranges studied. The ignition map can be a function of TPS or of MAP. The MAP is best applied to our case, because the equipment has better resolution to it than to TPS, concerning the sensitivity to the pressure variation in the collector, needed to build the map. With the modifications introduced (ignition map, gas reservoir and thermal insulation) the gasifier efficiency was increased up to 18%, the efficiency of the generator / group by 5% and the thermal efficiency of the system by 9%, compared to what had been achieved by RUMÃO (2013), in addition to reducing fuel consumption to the same achieved power.